KELURAHAN TALANG MANDI KECAMATAN MANDAU KABUPATEN BENGKALIS - Ningsih, Penti Rahayu; Marnelly, Tengku Romi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Smoking behavior among the adults become commonplace. Smoking is a lifestylephenomenon in the present so as regards the behavior of smoking as a behavior that is reasonableand does not have a problem. Behavior smoking can be found everywhere and from various agecircle namely from adult to children. For the moment many women have found the smokingbehavior and in this study women were mothers. The social behavior of a relative nature torespond to others in a way that is different. As social beings, smoking behavior is a behavior thatcan not be separated from other human. The smoking behavior is heavily influenced by the socialenvironment due to the behavior or character of a person likely to be formed by the surroundingenvironment. This study has several purposes for the researchers themselves as well as for otherstudents. The purpose of this study was first held to find out about the social behavior of motherswho smoked at Rt 02 Rw 14 TalangMandi village. The second objective is to determine thefactors that influence smoking behavior of these mothers. Analyzing the data in this study usinga qualitative descriptive study method. This study aims to identify and describe socialphenomena as well as trying to analyze it in accordance with the reality based on the dataobtained. Subjects in this study determined Snowball Sampling. Informants in this study werewomen's status as mothers of 5 people who have the habit of smoking. Methods of datacollection that is by observation and interviews. The study was conducted in Duri RT 02 Rw 14TalangMandi village Mandau sub Bengkalis. The results show that the social behavior ofmothers who smoke are mothers smoked openly namely smoking environment sesame smokersand smoke in the environment of people who do not smoke. Only one person mothers are stillconsidering the smoking behavior when with other people either smoke or not smoke. Thefactors that affect mothers smoke are penggaruh to friends who smoke other than that motherswho smoke live and hang out amid people who are also characterized by other factors, namelysmoking and stress.Keywords: Social Behavior, Smoke, Mothers